2012
DOI: 10.1155/2012/939620
|View full text |Cite
|
Sign up to set email alerts
|

Natural Convection in an Inclined Porous Cavity with Spatial Sidewall Temperature Variations

Abstract: The natural convection in an inclined porous square cavity is investigated numerically. The left wall is assumed to have spatial sinusoidal temperature variations about a constant mean value, while the right wall is cooled. The horizontal walls are considered adiabatic. A finite difference method is used to solve numerically the nondimensional governing equations. The effects of the inclination angle of the cavity, the amplitude and wave numbers of the heated sidewall temperature variation on the natural conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Sathiyamoorthy and Chamkha (Behseresht et al, 2014;Saeid and Mohamad, 2005;Saeid and Yaacob, 2006) considered natural convection in a square cavity for linearly heated side walls. Selamat et al (2012) Spatial sidewall temperature variations investigated the effect of inclination angle on natural convection in a porous cavity with spatial sidewall temperature variations. However, the study of natural convection heat transfer in a trapezoidal cavity filled with nanofluid and heated by spatial sidewall temperature has not yet been undertaken.…”
mentioning
confidence: 99%
“…Sathiyamoorthy and Chamkha (Behseresht et al, 2014;Saeid and Mohamad, 2005;Saeid and Yaacob, 2006) considered natural convection in a square cavity for linearly heated side walls. Selamat et al (2012) Spatial sidewall temperature variations investigated the effect of inclination angle on natural convection in a porous cavity with spatial sidewall temperature variations. However, the study of natural convection heat transfer in a trapezoidal cavity filled with nanofluid and heated by spatial sidewall temperature has not yet been undertaken.…”
mentioning
confidence: 99%
“…Their results revealed that the dynamic and temperature fields are strongly affected by the variations of magnetic field and the inclination angle. The maximum natural convection state significantly depends on the angle of inclination which was found by Selamat et al (2012).…”
mentioning
confidence: 89%
“…Detailed reviews of convection heat transfer applications in a porous media are reported in the recently published books by Pop and Ingham [1], Vafai [2], Ingham and Pop [3] and Nield and Bejan [4]. During the past years, many studies considered the free convection in cavities filled with the porous media [5][6][7][8][9][10][11][12]. Furthermore, the analysis of the joint conduction and free convection heat transfer in a cavity filled with a porous media received great concern by considerable number of investigators as it is widely found in practical applications such as buildings isolation, double-glazing windows, electronic devices cooling and cold storage installations.…”
Section: Introductionmentioning
confidence: 99%